HUBUNGAN ANTARA SIKAP BELAJAR MAHASISWA DENGAN PRESTASI BELAJAR MATA KULIAH ETIKA PROFESI - Tustiyana Windiyani; Yudhie Suchyadi (Universitas Pakuan, 2020)
THE CORRELATION BETWEEN STUDENTS LEARNING ATTITUDE AND LEARNING ACHIEVEMENTThis research belongs to quantitative research with correlational study type which consist of student learning attitude as independent variable and learning achievement as dependent variable. The purpose of this study to determine the positive relationship Between Student Attitude Learning With Achievement Learning. The data of this research were obtained by using Likert scale questionnaire for learning attitude variable and job result data, quiz, UTS and UAS for learning achievement. The instrument validity test of learning attitude and learning achievement was calculated using Product Moment Pearson formula and for reliability test was calculated using Alpha Cronbach formula. The population in this study are students of Semester V class F, G, and H Program Study PGSD academic year 2016/2017. That numbered 95 students. Samples were drawn by 49 students, obtained by using Taro Yamane formula with 10% precision. This quantitative research is done by testing the validity and reliability of the instrument which is then followed by surveying the sample with valid and reliable instruments. Then, the results showed that there is a relationship between learning attitudes with the achievement of the subject of Professional Ethics, shown by statistical analysis resulting in correlation coefficient price (rxy) of 0.97 shows the relationship between student learning attitudes with learning achievement, while the coefficient of determination (r2) of 0.94 or 94%. This means learning achievement of 94% results in correlation with learning attitudes, through regression equation ie Ŷ = (- 22,78 + 0,81). The remaining 6% is influenced by other factors.